A longitudinal study of gross motor coordination and weight status in children. (6th March 2014) - D'Hondt, Eva; Deforche, Benedicte; Gentier, Ilse; Verstuyf, Joke; Vaeyens, Roel; De Bourdeaudhuij, Ilse; Philippaerts, Renaat; Lenoir, Matthieu
<x xml:space="preserve">Abstract</x> Objective This longitudinal study investigated the interrelationship between children's weight status and level of gross motor coordination over time, taking baseline physical activity (PA) into account as a possible mediator. Methods Baseline measurements were collected in 2517 children (5‐13 years, 52.8% boys), including (1) body height and weight to calculate body mass index (BMI) z‐scores, (2) gross motor coordination using the Körperkoordinationstest für Kinder (KTK), (3) total PA estimated by a questionnaire. At follow‐up, 754 participants (7‐13 years, 50.8% boys) underwent anthropometric and KTK assessments again. Two hypothesized partial mediation models (i.e., KTK ↔ PA ↔ BMI z‐score) were examined by multiple linear mixed models. Results A lower performance on the KTK at baseline significantly predicted an increase in BMI z‐score (B = −0.003, P = 0.027). Conversely, a higher baseline BMI z‐score also predicted a decrease in KTK performance (B = −1.792, P < 0.001). Since total PA at baseline was not significantly related to initial KTK performance (B = 1.628, P = 0.134) nor BMI z‐score (B = 25.312, P = 0.130), its mediating effect was not further explored. Conclusions Our results strongly suggest that children's weight status negatively influences future level of gross motor coordination, and vice versa. Prevention and intervention initiatives should consider this reciprocal causal relationship across developmental time.